An Improved Numerical Simulation Approach for the Failure of Rock Bolts Subjected to Tensile Load in Deep Roadway. (10th October 2020) - Wang, Rui; Bai, Jian-biao; Yan, Shuai; Song, Yuan-ba; Wang, Guang-dong
Abstract : Our goal was to develop an effective research tool for roadways with significant deformations supported by rock bolts. The improved numerical simulation approach is constructed through additional development of FLAC3D. The aim is to modify the shortcoming that the original model in FLAC3D regards the plastic tensile strain of any arbitrary rock bolt element node as the rupture discrimination criterion. The FISH programming language is adopted to conduct the secondary development and to embed the revised model into the main program of FLAC3D. Taking an actual mining roadway as the simulation object, two simulation schemes adopting the newly improved approach and the original method were conducted, respectively. The results show that (1) the PILE element that constitutes the rock bolt-free section with the maximum elongation rate ruptures after modification, while the rock bolt tendon elongation rate reaches beyond the predefined tensile rupture elongation rate; (2) the modified model in which the rock bolt is mainly subjected to tension realises the tensile rupture phenomenon at the end of the rock bolt-free section and the rock bolt at the junction between the free section and the anchoring section; and (3) only four rock bolts that are in the roadway sides showed rupture in the modified model, and all rock bolts showed rupture in the original model. The tensile failure of the rock bolt led that the modified model scheme is closer to the actual. Compared with the modified model, in the original model, deformation of the surrounding rock masses is severe. This is resulted by the rupture of all rock bolts in the original model. The analysis shows that the improved numerical simulation approach is much more reliable for large deformation roadway behavior with rock bolt support.